Transforming Passion into Business: A Literature Review of Intrinsic Motivation and Creative Ideas in Entrepreneurial Venture Creation - Theresia Yunindri Trianna Sion; I Made Adi Putra Astman; Ichal Rizkiansyah; Maria Iki Kehi; Enike Tje Yustin Dima (International Journal of Information System and Innovation Management (IJISIM), 2026)
Digitalization has become an unavoidable trend for Micro, Small, and Medium Enterprises (MSMEs) to ensure business sustainability and competitiveness in both domestic and international markets. However, MSMEs face significant organizational and technological barriers, including limited financial resources, lack of management support, and inadequate infrastructure. This study aims to analyze the influence of digital transformation, entrepreneurial motivation, and creativity on the market competitiveness of MSMEs. Using a qualitative literature review methodology, this research explores how technologies such as Artificial Intelligence (AI) and strategic agility function as enablers for innovation. The results indicate that digital transformation creates a new digital entrepreneurial ecosystem that enhances operational efficiency and market reach. Furthermore, intrinsic motivation and creativity are crucial internal factors that significantly drive the interest and success of entrepreneurs in navigating market uncertainties. The findings suggest that a synergy between visionary leadership, a supportive organizational culture, and robust technological infrastructure is essential for successful digital adaptation.